Cobalt-doped zinc oxide nanofiber, preparation method thereof and listeria monocytogenes detection method

The detection of 3H-2B gas by cobalt-doped zinc oxide nanofibers has solved the problem of expensive and time-consuming equipment for existing Listeria detection methods and equipment, and achieved rapid and highly sensitive detection of Listeria, satisfying the disease-causing in food Requirements for bacteria detection.

CN119194666APending Publication Date: 2024-12-27CIVIL AVIATION UNIV OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411255730.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing Listeria detection methods and equipment are expensive, time-consuming, low sensitivity, and strict experimental conditions, which cannot meet the needs of rapid and sensitive detection of pathogenic bacteria in food.

Method used

Cobalt-doped zinc oxide nanofibers are used to detect 3-hydroxy-2-butanone gas to achieve rapid detection of Listeria, improving the sensitivity and selectivity of ZnO gas sensors. The nanofibers are prepared by electrospinning technology, using N,N-dimethylformamide and polyvinylpyrroleenone to dissolve zinc nitrate hexahydrate and cobalt acetate tetrahydrate, and dried and calcined to form an efficient gas-sensitive material.

Benefits of technology

It realizes rapid response and high sensitivity detection of Listeria biomarker 3H-2B gas, with a response speed of up to 1s and a sensitivity of up to 168. It has great application potential and significantly improves the selectivity and stability of the sensor. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194666A_ABST
    Figure CN119194666A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of microbial monitoring, and discloses a cobalt-doped zinc oxide nanofiber and a preparation method thereof.The preparation method comprises the steps that firstly, polyvinylpyrrolidone (PVP) is added into an N, N-dimethylformamide (DMF) solution, zinc nitrate hexahydrate and cobaltous acetate tetrahydrate are added after the PVP is evenly dissolved, and the PVP and the cobaltous acetate tetrahydrate are stirred to be evenly dissolved; then carrying out electrostatic spinning on the obtained precursor solution; carrying out drying treatment on a membrane obtained by electrostatic spinning; finally, the dried membrane is subjected to calcination treatment; the cobalt-doped zinc oxide nanofiber can be used for preparing a gas sensor for detecting a biomarker 3-hydroxy-2-butanone gas of listeria monocytogenes. The Co-ZnO nano-fiber has excellent gas sensitivity to the biomarker 3H-2B, the response speed is high, the sensitivity is high, the Listeria monocytogenes are monitored by detecting the 3H-2B gas through the Co-ZnO nano-fiber, the possibility is provided for real-time monitoring of the Listeria monocytogenes, and the Co-ZnO nano-fiber has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microbial monitoring, and in particular, relates to a method for preparing cobalt-doped zinc oxide nanofibers, and a method for detecting Listeria using the cobalt-doped zinc oxide nanofibers. Background Art

[0002] Food safety has increasingly become a focus of attention for people around the world. Foodborne diseases are a major food safety issue, mainly caused by pathogenic microorganisms such as Listeria that are widely present in nature. Listeria monocytogenes is often detected in refrigerated foods and raw poultry, and it has a much higher tolerance to low temperatures than other foodborne pathogens. Listeria infection can often cause fever, headache, and gastrointestinal manifestations such as vomiting, nausea, and diarrhea. In addition, some individuals may also experience serious complications, including meningoencephalitis or sepsis, with a mortality rate of up to 20%-30%. Rapid and highly sensitive detection of Listeria is the key to reducing the risk of Listeria infection and preventing and treating diseases such as meningitis and endocarditis caused by Listeria!

[0003] At present, the methods used to detect Listeria mainly include nucleic acid detection, real-time PCR, separation and culture biochemical identification method (USDA, FDA), immunological method (ELISA, IGLT), mass spectrometry, etc., but these methods are not only time-consuming, but also the equipment is relatively expensive. For example, the USDA method is to first enrich the bacteria in UVM modified broth medium; then use Fraser broth medium for secondary enrichment culture, take the enrichment liquid and selectively separate and culture on modified Oxford agar (MOX) plate; take monoclonal colonies and culture on horse blood agar (HL) to observe whether there is a β-hemolytic ring. If there is, pick the monoclonal colony for brain heart infusion (BHI) and dynamic test culture, and finally perform biochemical and serological identification. This method is cumbersome to operate, has a large workload, and a long detection cycle (generally 4-7 days). In this cumbersome process, any error in any link may affect the identification results of bacteria, with low sensitivity, high missed detection and false detection rates. In addition, this method has strict requirements on experimental conditions. Therefore, it cannot meet the needs of rapid and sensitive detection of pathogenic bacteria in food. ELISA is a detection method based on the characteristics of antigen-antibody specific binding, using special enzyme markers to qualitatively or quantitatively analyze the substance to be tested. It is the most widely used technology in enzyme immunoassay technology. The ELISA detection method has the characteristics of accuracy, specificity, sensitivity, and repeatability, but there are still some disadvantages that cannot be ignored, such as the cumbersome antibody preparation and purification process, easy to produce false positives, greatly affected by temperature and time, and expensive purchase of enzyme-labeled antibodies. These shortcomings limit the wide application of ELISA detection methods in on-site detection. PCR is a molecular biology technology for amplifying specific DNA fragments based on nucleic acid molecular hybridization. It includes ordinary PCR, nested PCR, fluorescent quantitative PCR, multiplex PCR, RT-PCR and immune PCR. The high specificity of the PCR reaction is attributed to the high specificity of the primers, so for the PCR reaction, the design of the primers is particularly critical. If the design is unreasonable, false negative and false positive results are likely to occur. In addition, the expensive reagents and the need for pre-enrichment of samples are also disadvantages that cannot be ignored in this detection method. Summary of the invention

[0004] In view of the shortcomings of existing Listeria detection methods such as expensive equipment and long time consumption, the present invention provides a cobalt-doped zinc oxide nanofiber and a preparation method thereof, and utilizes the cobalt-doped zinc oxide nanofiber to detect 3-hydroxy-2-butanone (3H-2B) gas, thereby realizing a method for detecting Listeria and improving the sensitivity and selectivity of ZnO gas sensors.

[0005] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:

[0006] According to a first aspect of the present invention, there is provided a cobalt-doped zinc oxide nanofiber, which is prepared by the following preparation method:

[0007] S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc nitrate hexahydrate and cobalt acetate tetrahydrate after dissolving evenly, and stir to dissolve evenly;

[0008] S2, electrospinning the precursor solution obtained in S1;

[0009] S3, drying the film obtained in S2;

[0010] S4, calcining the film obtained in S3.

[0011] According to a second aspect of the present invention, there is provided a method for preparing cobalt-doped zinc oxide nanofibers, comprising:

[0012] S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc nitrate hexahydrate and cobalt acetate tetrahydrate after dissolving evenly, and stir to dissolve evenly;

[0013] S2, electrospinning the precursor solution obtained in S1;

[0014] S3, drying the film obtained in S2;

[0015] S4, calcining the film obtained in S3.

[0016] For the above-mentioned cobalt-doped zinc oxide nanofibers and preparation methods thereof:

[0017] Preferably, in S1, the mass ratio of the N,N-dimethylformamide (DMF) to the polyvinylpyrrolidone (PVP) is (10-11):1.

[0018] Preferably, in S1, the mass ratio of the zinc nitrate hexahydrate to the polyvinyl pyrrolidone (PVP) is (1-2):1.

[0019] Preferably, in S1, the molar ratio of Co in the cobalt acetate tetrahydrate to Zn in the zinc nitrate hexahydrate is ≤5% and is not 0.

[0020] Preferably, in S2, the feed rate of the electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.

[0021] Preferably, in S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.

[0022] Preferably, in S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, and keep the temperature for 2-4h, and then naturally cool to room temperature.

[0023] According to a third aspect of the present invention, a method for detecting Listeria is provided, which uses the above-mentioned cobalt-doped zinc oxide nanofibers to detect 3-hydroxy-2-butanone gas, a biomarker of Listeria.

[0024] According to a fourth aspect of the present invention, a gas sensor for Listeria detection is provided, which uses the above-mentioned cobalt-doped zinc oxide nanofiber as a gas-sensitive material.

[0025] The beneficial effects of the present invention are:

[0026] The Co-ZnO nanofibers prepared by the present invention have excellent gas-sensing performance for the biomarker 3H-2B, fast response speed, and high sensitivity. 3H-2B gas is a biomarker of Listeria metabolism. The present invention monitors Listeria by detecting 3H-2B gas through Co-ZnO nanofibers, which provides the possibility for real-time monitoring of Listeria and has great application potential. Among them, the diameter of 0.5% Co-ZnO nanofibers is about 62nm. The gas-sensing performance test results show that the material has high selectivity, a response speed of up to 1s, and a sensitivity of up to 168. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart of the preparation of Co-doped ZnO nanofibers and gas sensors thereof;

[0028] Figure 2 The response curves of the gas sensors prepared from the samples obtained in Examples 1-6 to 100 ppm 3H-2B at different operating temperatures;

[0029] Figure 3 The response curve of the gas sensor prepared from the samples obtained in Examples 1-6 to 3H-2B gas of different concentrations at 305°C;

[0030] Figure 4 The continuous dynamic response-recovery curve diagram of the gas sensor prepared from the sample obtained in Example 3 of the present invention to different concentrations of 3H-2B (0.5-100 ppm) at 305°C;

[0031] Figure 5 The linear fitting relationship between the response of the gas sensor prepared from the sample obtained in Example 3 of the present invention to different concentrations of 3H-2B (0.5-100 ppm) at 305°C and the gas concentration;

[0032] Figure 6The dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 3 of the present invention to 100 ppm 3H-2B at 305°C;

[0033] Figure 7 This is a graph showing five sensitivity cycles of the gas sensor prepared from the sample obtained in Example 3 of the present invention at 305°C to 100ppm 3H-2B;

[0034] Figure 8 The selectivity test result diagram of the gas sensor prepared by the samples obtained in Examples 1-6 of the present invention to various gases at 100 ppm at 305°C;

[0035] Fig. 9 This is a long-term stability test diagram of a gas sensor prepared from a sample obtained in Example 3 of the present invention;

[0036] Fig.10 BET test results of (a) pure ZnO nanofibers and (b) 0.5% Co-ZnO nanofibers;

[0037] Fig.11 Schematic diagram of the gas sensor prepared from the sample obtained in Example 3 of the present invention for detecting 3H-2B;

[0038] Fig.12 This is the bandgap width test diagram of pure ZnO nanofibers and 0.5% Co-ZnO nanofibers. DETAILED DESCRIPTION

[0039] The following is a more detailed description of the specific implementation of the present invention in conjunction with the accompanying drawings and embodiments, so as to better understand the scheme of the present invention and its advantages in various aspects. It should be noted that the specific implementation methods and embodiments described below are only for the purpose of illustration, and are not intended to limit the present invention.

[0040] like Figure 1 As shown, the present invention adds DMF and PVP to a sample bottle, stirs at high speed, then adds zinc nitrate hexahydrate and a certain molar fraction of cobalt acetate tetrahydrate, stirs at high speed again, transfers the solution to a syringe, and fixes it on a peristaltic pump for electrostatic spinning. After electrostatic spinning, remove the sample film and dry it in a blast drying oven. After the dried sample is calcined in a muffle furnace, it is naturally cooled to room temperature. The collected samples are marked as ZnO, 0.05% Co-ZnO, 0.5% Co-ZnO, 1% Co-ZnO, 3% Co-ZnO, and 5% Co-ZnO.

[0041] For some preferred embodiments of the present invention, in S1, the mass ratio of N,N-dimethylformamide (DMF) to polyvinylpyrrolidone (PVP) is (10-11):1.

[0042] For some preferred embodiments of the present invention, in S1, the mass ratio of zinc nitrate hexahydrate to polyvinyl pyrrolidone (PVP) is (1-2):1.

[0043] For some preferred embodiments of the present invention, in S1, the molar ratio of Co in cobalt acetate tetrahydrate to Zn in zinc nitrate hexahydrate is ≤5% and is not 0.

[0044] For some preferred embodiments of the present invention, in S2, the feed rate of electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.

[0045] For some preferred embodiments of the present invention, in S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.

[0046] For some preferred embodiments of the present invention, in S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, and keep the temperature for 2-4h, and then naturally cool to room temperature.

[0047] Specifically:

[0048] Embodiment 1:

[0049] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0050] Step 2: Add 1 g of zinc nitrate hexahydrate to the obtained uniform solution, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0051] Step 3: Transfer the obtained solution into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine, set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0052] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0053] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the samples and mark them as ZnO.

[0054] Embodiment 2:

[0055] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0056] Step 2: Add 1 g of zinc nitrate hexahydrate and cobalt acetate tetrahydrate with Co(mol) / Zn(mol)=0.05% to the obtained uniform solution, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0057] Step 3: Transfer the obtained solution into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine, set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0058] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0059] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 0.05% Co-ZnO.

[0060] Embodiment 3:

[0061] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0062] Step 2: Add 1 g of zinc nitrate hexahydrate and cobalt acetate tetrahydrate with Co (mol) / Zn (mol) = 0.5% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0063] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0064] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0065] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 0.5% Co-ZnO.

[0066] Embodiment 4:

[0067] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0068] Step 2: Add 1 g of zinc nitrate hexahydrate and cobalt acetate tetrahydrate with Co(mol) / Zn(mol)=1% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0069] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0070] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0071] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 1% Co-ZnO.

[0072] Embodiment 5:

[0073] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0074] Step 2: Add 1 g of zinc nitrate hexahydrate and cobalt acetate tetrahydrate with Co(mol) / Zn(mol)=3% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0075] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0076] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0077] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 3% Co-ZnO.

[0078] Embodiment 6:

[0079] Step 1: First add 11 ml of DMF into a 20 ml sample bottle, then add 1 g of PVP, and stir at high speed (1000 rpm) on a magnetic stirrer for 4 hours to obtain a uniform solution.

[0080] Step 2: Add 1 g of zinc nitrate hexahydrate and cobalt acetate tetrahydrate with Co(mol) / Zn(mol)=5% to the homogeneous solution obtained above, and continue stirring at high speed (1000 rpm) on a magnetic stirrer for 12 h to ensure that the solution is fully mixed.

[0081] Step 3: Transfer the solution obtained in step 2 into a 10 ml syringe and fix it to the peristaltic pump of the electrospinning machine. Set the feed rate to 0.2 ml / h, the voltage to 15 kV, the distance from the needle to the collection drum to 14 cm, and the drum speed to 800 rpm.

[0082] Step 4: After the electrospinning is completed, remove the sample film and place it in a forced air drying oven at 80°C for 48 hours.

[0083] Step 5: Place the dried sample in a muffle furnace, set the heating rate to 2°C / min, heat to 600°C and keep it for 3 hours, then let it cool naturally to room temperature; collect the sample and mark it as 5% Co-ZnO.

[0084] Weigh 10-20 mg of the samples prepared in Examples 1-6 into a mortar, add a small amount of distilled water, and grind them thoroughly into a paste. Then, use a clean fine brush to evenly apply the paste on the ceramic tube of the gas sensor, dry it at 80°C for 5 hours, and then age it on an AS-20 aging device with a current of 80 mA for 48 hours to obtain six gas sensors to be tested.

[0085] Figure 2 The responses of six gas sensors are shown as a function of operating temperature. Figure 2As shown in the figure, with the increase of working temperature, the sensitivity of each gas sensor increases first and then decreases. The optimal working temperature of the six sensors is 305℃. Under the optimal working temperature conditions, the responses of ZnO, 0.05% Co-ZnO, 0.5% Co-ZnO, 1% Co-ZnO, 3% Co-ZnO, and 5% Co-ZnO to 100ppm 3H-2B are 31.3, 91.9, 168, 71.9, 94.2, and 71.56, respectively. Among them, 0.5% Co-ZnO has the highest sensitivity, while ZnO has the lowest response, indicating that Co doping significantly improves the sensing performance.

[0086] Figure 3 The responses of six gas sensors to different concentrations of 3H-2B at 305°C are shown. Figure 3 As shown in the figure, the response of each sensor increases linearly with the increase of 3H-2B concentration. In the range of 20-100ppm, 0.5% Co-ZnO has the highest response to 3H-2B, and its response to 100ppm 3H-2B is 5.26 times that of ZnO, indicating that Co doping significantly enhances the sensing of ZnO nanofibers. The responses of 0.5% Co-ZnO nanofibers to 0.5, 1, 2, 5, 10, 20, 50 and 100ppm 3H-2B are 1.81, 2.41, 3.38, 6.44, 15.41, 33.25, 87.23 and 168.5, respectively.

[0087] Figure 4 The following is a continuous dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 3 to different concentrations of 3H-2B (0.5-100 ppm) at 305°C. Figure 4 As shown in Figure 3, the response of 0.5% Co-ZnO increases with the increase of 3H-2B concentration. 0.5% Co-ZnO exhibits excellent recovery ability, and its response can quickly return to the baseline level when exposed to air.

[0088] The response of the gas sensor prepared with 0.5% Co-ZnO to different concentrations of 3H-2B was evaluated by linear regression analysis. The linear fitting relationship between the response and the gas concentration is shown in Figure 5 The fitted linear equation is y=1.699x-0.40966, and the correlation coefficient (R) is 0.99887, indicating that the sensor's response to different concentrations of 3H-2B has a good linear relationship with the gas concentration.

[0089] Figure 6 The dynamic response-recovery curve of the gas sensor prepared from the sample obtained in Example 3 to 100 ppm 3H-2B at 305°C. Figure 6As shown, at 305°C, the response time of 0.5% Co-ZnO nanofibers to 100 ppm 3H-2B is 1 s, and the recovery time is 222 s.

[0090] At 305°C, the gas sensor prepared with 0.5% Co-ZnO was subjected to dynamic response-recovery tests for 100ppm 3H-2B for 5 consecutive times. The test results are shown in Figure 2. Figure 7 After 5 cycles, the sensor's response to 3H-2B showed good stability and recovery ability, and the overall response remained basically unchanged.

[0091] Figure 8 The responses of gas sensors prepared by ZnO, 0.05% Co-ZnO, 0.5% Co-ZnO, 1% Co-ZnO, 3% Co-ZnO and 5% Co-ZnO to 100ppm target gas at 305℃ are shown. Among them, the response of each gas sensor to 100ppm 3H-2B is the highest, while the response to other gases is very low, indicating that this series of sensors has significant selectivity for 3H-2B gas. Among them, the response value of 0.5% Co-ZnO nanofibers to 3H-2B is 168, and the response values ​​to acetone, triethylamine, methanol, ethanol, dichloroethane, n-butanol, isopropanol and ammonia are 40.03, 32.4, 38.13, 38, 43, 64, 35 and 9.69 respectively.

[0092] In order to test the long-term stability of the sensor, the gas sensor prepared with 0.5% Co-ZnO was tested for the response to 100ppm 3H-2B at 305°C for 15 consecutive days. Fig. 9 As shown, it can be seen that the response of the sensor fluctuates slightly within 15 days, showing excellent long-term stability.

[0093] The specific surface area and pore size distribution of ZnO nanofibers and 0.5% Co-ZnO nanofibers were studied by N2 adsorption-desorption technique. The BET test results are shown in Fig.10 As shown in the test results, the specific surface area of ​​ZnO is 9.467m 2 / g, while the specific surface area of ​​0.5% Co-ZnO is slightly larger, which is 10.513m 2 / g. This means that in the gas sensing process, 0.5% Co-ZnO can provide more active sites for gas molecules, thereby achieving higher sensitivity. According to the IUPAC standard, the pore type of ZnO and 0.5% Co-ZnO is H3 type, with plate seams, cracks, and wedge-shaped structural characteristics. In addition, the pore volume-pore distribution curve shows that the pore concentration of 0.5% Co-ZnO in the range of 2 to 5 nm is higher than that of ZnO.

[0094] Fig.11 The schematic diagram of the gas sensor prepared from the sample obtained in Example 3 of the present invention to detect 3H-2B. When the temperature is lower than 150°C, the oxygen adsorbed on the MOS surface is mainly in the form of O2 - In the range of 150℃-400℃, the adsorbed oxygen of sensitive substances is mainly O - ; When the temperature is higher than 400℃, the adsorbed oxygen is mainly O 2- 0.5% Co-ZnO has the characteristics of n-type MOS, which conducts electricity mainly through electrons. Since oxygen has a strong electronegativity in the air, oxygen molecules will be adsorbed on the surface of 0.5% Co-ZnO and react with electrons in its conduction band to form oxygen ions. As shown in the figure, at 305°C, the oxygen adsorbed on the surface of 0.5% Co-ZnO is mainly O - , resulting in the formation of an electron depletion layer (EDL) on the surface of 0.5% Co-ZnO, increasing its resistance (a) and grain boundary barrier (c). When the sensor detects 3H-2B, the adsorbed oxygen ions react with the 3H-2B molecules, releasing electrons back into the material, reducing the EDL width (b) and grain boundary barrier (d), while also reducing resistance.

[0095] Fig.12 The figure shows the bandgap test of pure ZnO nanofibers and 0.5% Co-ZnO nanofibers. The UV-Vis test results show that the bandgap of 0.5% Co-ZnO is 3.15eV, while the bandgap of pure ZnO nanofibers is 3.25eV, which means that under the same temperature conditions, 0.5% Co-ZnO nanofibers will be able to excite more carriers and exchange electrons with more oxygen, thereby effectively enhancing the gas sensing performance.

[0096] Although the preferred embodiments of the present invention have been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative and not restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms of specific changes without departing from the scope of protection of the invention and the claims, all of which fall within the scope of protection of the present invention.

Claims

1. A method for preparing cobalt-doped zinc oxide nanofibers, characterized in that: include: S1. Add polyvinyl pyrrolidone (PVP) to N,N-dimethylformamide (DMF), and then add zinc nitrate hexahydrate and cobalt acetate tetrahydrate after dissolving evenly, and stir to dissolve evenly; S2, electrospinning the precursor solution obtained in S1; S3, drying the film obtained in S2; S4, calcining the film obtained in S3.

2. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S1, the mass ratio of the N,N-dimethylformamide (DMF) to the polyvinylpyrrolidone (PVP) is (10-11):

1.

3. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S1, the mass ratio of the zinc nitrate hexahydrate to the polyvinyl pyrrolidone (PVP) is (1-2):

1.

4. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S1, the molar ratio of Co in the cobalt acetate tetrahydrate to Zn in the zinc nitrate hexahydrate is ≤5% and is not 0%.

5. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S2, the feed rate of the electrospinning is 0.1-0.3 ml / h, the voltage is 13-18 kV, the distance from the needle to the collecting drum is 11-15 cm, and the drum speed is 800-1000 rpm.

6. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S3, the drying process is carried out at a temperature of 60-100°C and for a time of 36-48 hours.

7. The method for preparing cobalt-doped zinc oxide nanofibers according to claim 1, characterized in that: In S4, the calcination process is to increase the temperature to 500-700°C at a heating rate of 1-3°C / min, keep the temperature for 2-4h, and then naturally cool to room temperature.

8. A cobalt-doped zinc oxide nanofiber, characterized in that: Obtained by the preparation method according to any one of claims 1 to 7.

9. A method for detecting Listeria monocytogenes, characterized in that: The cobalt-doped zinc oxide nanofibers as described in claim 8 are used to detect 3-hydroxy-2-butanone gas, a biomarker of Listeria.

10. A gas sensor for Listeria detection, characterized in that: The cobalt-doped zinc oxide nanofiber as claimed in claim 8 is used as a gas-sensitive material.